Use and Product Characteristics of "Tobacco Free Nicotine" E-Cigarettes Among Young Adults. Issue 3 (1st August 2022) - Davis, Danielle R; Bold, Krysten W; Camenga, Deepa; Kong, Grace; Jackson, Asti; Lee, Juhan; Rajesh-Kumar, Lavanya; Krishnan-Sarin, Suchitra; Morean, Meghan E
Abstract: Introduction: E-cigarettes are increasingly being marketed as containing tobacco-free nicotine (TFN). There is no data examining use of TFN e-cigarettes by young adults and how use may differ from non-TFN e-cigarettes. The current study aims to characterize young adult TFN e-cigarette use and examine differences between those who report using TFN and non-TFN e-cigarettes. Method: U.S. young adults (18–25) with lifetime e-cigarette use ( n = 927) were recruited via online panels in Fall 2021 and answered questions about TFN and non-TFN e-cigarettes. Participants were categorized by lifetime TFN e-cigarette use status (yes vs. no; 34% yes). Bivariate comparisons examined differences in e-cigarette characteristics (device type, flavors, nicotine concentration) between the TFN and non-TFN groups. Binary logistic regression models examined associations between lifetime frequency of vaping (<100 vs. ≥100 times), and other tobacco product, cannabis, and/or alcohol use and lifetime TFN e-cigarette use (yes vs. no). Adjusted models include age, race/ethnicity, vaping onset age, and sex. Results: In multivariable adjusted models, lifetime TFN e-cigarette use was associated with younger age, greater lifetime vaping, and nicotine pouch use. Young adults who used TFN e-cigarettes were more likely to report fruit, mint, menthol, and beverage flavors and know their e-liquid nicotine concentration compared with those who used non-TFN e-cigarettes. Conclusion: Among young adults who have used e-cigarettes, more frequent e-cigarette use and use of nicotine pouches, which can also contain TFN, were associated with TFN e-cigarette use. Understanding behaviors and characteristics of those using TFN e-cigarettes is critical to regulation of TFN containing products. Implications: This study characterizes young adults who report experience with tobacco free nicotine (TFN) e-cigarettes and compares them to those who have not used TFN e-cigarettes. Young adults with more frequent e-cigarette use and use of nicotine pouches are more likely to report TFN e-cigarette use.